A Divergent Approach to the Diastereoselective Synthesis of 3, 3‐Disubstituted Oxindoles from Atropisomeric N‐Aryl Oxindole Derivatives. Issue 22 (18th October 2016) - Nakazaki, Atsuo; Mori, Ayako; Kobayashi, Susumu; Nishikawa, Toshio
Abstract: 3, 3‐Disubstituted oxindoles were divergently synthesized by diastereoselective transformations including nucleophilic addition, alkylation, and cycloaddition using common, axially chiral N ‐aryl oxindoles. Notably, high diastereoselectivities (up to >95:5) were observed with ortho ‐monosubstituted N ‐aryl oxindoles to give various oxindole scaffolds, and facile removal of the p ‐(benzyloxy)aryl moiety in axially twisted amides was achieved by a mild, two‐step sequence. Abstract : 3, 3‐Disubstituted oxindoles were divergently synthesized by diastereoselective transformations including nucleophilic addition, alkylation, and cycloaddition using common, axially chiral N ‐aryl oxindoles. Notably, high diastereoselectivities (up to >95:5) were observed with ortho ‐monosubstituted N ‐aryl oxindoles to give various oxindole scaffolds, and facile removal of the p ‐(benzyloxy)aryl moiety in axially twisted amides was achieved by a mild, two‐step sequence.